Epitaxial Growth of Ferroelectric Pb(Zr, Ti)O3 Layers on GaAs. Issue 1675 (2014) - Meunier, Benjamin; Louahadj, Lamis; Le Bourdais, David; Largeau, Ludovic; Agnus, Guillaume; Lecoeur, Philippe; Pillard, Valérie; Mazet, Lucie; Bachelet, Romain; Regreny, Philippe; Botella, Claude; Grenet, Geneviève; et al.
ABSTRACT: Ferroelectric epitaxial Pb(Zr, Ti)O3 (PZT) layers were grown by pulsed laser deposition on SrTiO3 /GaAs templates fabricated by molecular beam epitaxy. The templates present an excellent structural quality and the SrTiO3 /GaAs is abrupt at the atomic scale thanks to surface Ti pre-treatment. The PZT layers contain a- and c- domains, as shown by X-Ray diffraction analyses. Piezoforce microscopy experiments and macroscopic electrical characterizations indicate that PZT is ferroelectric. A relative dielectric permittivity of 164 is extracted from these measurements.